Analisis Jurnal Elektronik Bidang Lingkungan Terakreditasi Tahun 2020 pada SINTA - Rochani Nani Rahayu; Sensusiyati (Jurnal IPI (Ikatan Pustakawan Indonesia), 2021)
Environmental problems are seen in the news. Scientific studies related to environmental problems are important in providing recommendations for solutions to environmental problems. The analysis of accredited electronic journals in the environmental field is carried out by descriptive methods, using data sources downloaded from http://issn.lipi.go.id/ and from http://sinta.ristekbrin.go.id/ with the aim of knowing: 1) Journal title and journal accreditation status; 2) Issuer; 3) Frequency of issue; 4) City of rise; 5) Journal citations. Furthermore the data is presented in tabular form for further analysis and conclusion drawing. The results of the study are known as many as 40 journal titles have been accredited with the level of SINTA 2 (22.50%), SINTA 3 (30%), SINTA 4 (27.50%), SINTA 5 (8%). Journal publishers are 27 state universities (67.50%), private universities 4 titles, (10%), state Islamic universities 1 (2.50%), public polytechnics 5 (12.50%), ministries 1 (2, 50%) and research institute 1 (2.50%) there is one professional association.( Asosiasi Pembina Hukum Lingkungan Indonesia). It is known that the frequency of publication of the journal is twice a year as many as 27 titles (67.50%), three times a year amounting to 9 (22, 50%), and four times a year 4 (10.00%). Bandung, Semarang, Jakarta, and Yogyakarta are the most published cities, each with 4 titles. There are three major journals which are widely cited, namely Enviroscienteae: Jurnal Ilmiah Bidang Pengelolaan Sumberdaya Alam dan Lingkungan (1,233 times), Jurnal Wilayah dan Lingkungan (1,294 times), and Jurnal Sumberdaya Alam dan Lingkungan (1,196 times). Research conclusions show that in Indonesia there are no accredited electronic journals at the SINTA level 1. Most publishers are state universities, and the Enviroscienteae : Jurnal Ilmiah Bidang Pengelolaan Sumberdaya Alam dan Lingkungan , published by the Bogor Institute of Agriculture, is the most cited journal (1,233 times).